Web-based system on pregnancy - giving birth (Sistem Kehamilan - Kelahiran Anak) / Siow Hoi Yen - Siow , Hoi Yen (2000)
From pregnancy until childbirth, it is always a process of tiring, joy and tribulations. Pregnancy women experience great changes in mentality and physically. They need to learn the related information to minimize their anxiety, to help them discover the danger signs earlier and to be well prepared for their baby's arrival. In Malaysia, pregnancy women tend to get the knowledge on pregnancy from their relatives, friends and books. An online system on pregnancy - giving birth could be developed as a good alternative of their information resources. The information could be delivered via World Wide Web (WWW). With the features of easy accessibility, interactivity, existence of multimedia elements (audio, video, animation, text and graphic), user friendliness and published in Malay version, Malaysian pregnancy women could learn the related knowledge in a better way. Several surveys and research had done to do assessment and review about the system. System Development Life Cycle used as a methodology of the proposed project. The data to be presented includes text data, still images, video data and animated graphics. This information would be refined by expertise. A database also has to be implemented for storing the data that would be retrieved for display and captured from users.